2012
DOI: 10.1016/j.biomaterials.2012.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Diminished adhesion and activation of platelets and neutrophils with CD47 functionalized blood contacting surfaces

Abstract: CD47 is a ubiquitously expressed transmembrane protein that, through signaling mechanisms mediated by signal regulatory protein alpha (SIRPα1), functions as a biological marker of ‘self-recognition’. We showed previously that inflammatory cell attachment to polymeric surfaces is inhibited by the attachment of biotinylated recombinant CD47 (CD47B). We test herein the hypothesis that CD47-modified blood conduits can reduce platelet and neutrophil activation under clinically relevant conditions. We appended a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 40 publications
5
74
2
Order By: Relevance
“…63 Using an ex vivo model system, which perfuses whole blood over CD47 immobilized or unmodified control surfaces, we showed that platelet activation was significantly inhibited as a function of CD47 exposure. 63 Specifically, we showed that the expression of the protein surface marker of platelet activation, P-selectin (CD62P), was significantly reduced after 3 h exposure to CD47-modified blood conduits. 63 Scanning electron microscopy demonstrated that the platelet attachment was markedly reduced on CD47-modified surfaces compared with unmodified control surfaces.…”
Section: Cd47-sirpa Signaling and Phagocytosismentioning
confidence: 89%
“…63 Using an ex vivo model system, which perfuses whole blood over CD47 immobilized or unmodified control surfaces, we showed that platelet activation was significantly inhibited as a function of CD47 exposure. 63 Specifically, we showed that the expression of the protein surface marker of platelet activation, P-selectin (CD62P), was significantly reduced after 3 h exposure to CD47-modified blood conduits. 63 Scanning electron microscopy demonstrated that the platelet attachment was markedly reduced on CD47-modified surfaces compared with unmodified control surfaces.…”
Section: Cd47-sirpa Signaling and Phagocytosismentioning
confidence: 89%
“…Reducing the covalently appended PDT groups with tris(2-carboxyethyl) phosphine hydrochloride (TCEP) 11 yields a thiolated surface that can be subsequently reacted with therapeutic moieties. Detailed herein and previously 12,13 , recCD47, further modified with the addition of a C-terminal poly-lysine tail 12,13 , is reacted with Sulfosuccinimidyl-4-[Nmaleimidomethyl]cyclohexane-1-carboxylate (sulfo-SMCC) for 1 hr to generate thiol-reactive groups, allowing for a monosulfide bond formation between the tubing and recCD47 11 . The anti-inflammatory capacity of the CD47 functionalized surfaces was tested, ex vivo, using the Chandler Loop Apparatus with whole human blood, which was originally described in 1958 as an in vitro model of thrombotic coagulation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Signal-regulatory protein alpha (SIRPα), the cognate receptor for CD47, and a member of the immunoreceptor tyrosine-based inhibitory motif (ITIM)-containing family of transmembrane proteins, is expressed on cells of myeloid origin 14 . We have previously demonstrated that CD47, via SIRPα-mediated cell signaling, down-regulates the immune responses to polyurethane (PU) and polyvinylchloride (PVC) in in vitro, ex vivo, and in vivo models [11][12][13] . Central to our investigations is a relatively novel photoactivation chemistry, described herein, in which chemically reactive thiol groups are covalently appended to polymeric tubing by reacting the tubing with a multifunctional polymer (PDT-BzPh), composed of 2-pyridyldithio (PDT), the photoreactive benzophenone (BzPh) and a carboxy-modified polyallylamine [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations